PENDIDIKAN KELUARGA : ANALISIS PENDIDIKAN KELUARGA DALAM MUATAN DO'A IBRAHIM A.S - Aida Arini; Shobihus Surur (EL-Islam, 2019)
A family is a group of two people or more who are related by blood, marriage road option. It is a place for children to grow and to progress. To be a kind self- need process. Family- education process can influence children's growth. It is done by parents to their children as their responsibility and hope. The education process must be true. The wrong process makes bad children. To educate well, we can learn an example of Ibrahim's as way, his success in educating and guiding his family. His way to educate did not only talk, advice, give an example but also to recite the aim in his prayer.